👤

Ustal, które z poniższych wyrażeń przyjmuje wartość zero.

a)3xy+[tex]y^{2}[/tex]+8-2xy-6-xy -2y

b)x-y+3y-x-3

c)[tex]x^{2}[/tex] +4xy-xy-[tex]x^{2}[/tex] -3xy

d)2x-4xy+2y
Pls szybko dam 10 bo mam mało


Odpowiedź :

Odpowiedź:

[tex]a)\ \ 3xy+y^2+8-2xy-6-xy-2y=y^2-2y+2\\\\b)\ \ x-y+3y-x-3=2y-3\\\\c)\ \ x^2+4xy-xy-x^2-3xy=4xy-4xy=0\\\\d)\ \ 2x-4xy+2y\\\\Odp.C[/tex]

Odpowiedź:

Szczegółowe wyjaśnienie:

a)

3xy+y²+8-2xy-6-xy-2y=3xy-2xy-xy+y²+8-6-2y=xy+y²+2-2y

b)

x-y+3y-x-3=x-x-y+3y-3=2y-3

c)

x²+4xy-xy-x²-3xy=x²-x²+4xy-xy-3xy=0

d)

2x-4xy+2y